2018
DOI: 10.1111/zph.12518
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of locally acquired spotted fever group rickettsioses in Southeast Texas, 2008–2016

Abstract: We identified six paediatric case-patients from southeast Texas diagnosed with confirmed or probable Spotted Fever Group Rickettsiosis (SFGR) between 2008 and 2016. Only one case had a history of travel to an endemic area. Clinical and laboratory findings strongly suggest locally acquired Rocky Mountain Spotted Fever in one Houston patient. Public health reporting of SFGR is critical for monitoring emergence in nonendemic regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Researchers of recent studies have shown more infections with Rickettsia as well as confirmed autochthonous transmission of spotted fever group rickettsioses in Houston. 25,26 In these studies, relatively few instances of Rickettsia infections were followed with convalescent serological testing, although in every case in which convalescent testing was conducted, fourfold conversion confirming infection occurred. 27 For this reason we chose to include these infections as causes of encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers of recent studies have shown more infections with Rickettsia as well as confirmed autochthonous transmission of spotted fever group rickettsioses in Houston. 25,26 In these studies, relatively few instances of Rickettsia infections were followed with convalescent serological testing, although in every case in which convalescent testing was conducted, fourfold conversion confirming infection occurred. 27 For this reason we chose to include these infections as causes of encephalitis.…”
Section: Discussionmentioning
confidence: 99%